WEBVTT
00:00:01.050 --> 00:00:06.580
Find the inverse of the function π of π₯ equals the cube root of two minus π₯.
00:00:07.180 --> 00:00:10.070
The first thing we wanna do is replace π of π₯ with π¦.
00:00:10.680 --> 00:00:13.350
Now weβre going to interchange π₯ and π¦.
00:00:14.140 --> 00:00:18.910
So π₯ is equal to the cube root of two minus π¦, and now we will solve for π¦.
00:00:19.450 --> 00:00:24.120
So the first thing that we need to do is to cube both sides to get rid of the cube root.
00:00:24.650 --> 00:00:28.250
So now we have π₯ cubed equals two minus π¦.
00:00:28.990 --> 00:00:32.450
So letβs first subtract two to both sides.
00:00:32.830 --> 00:00:36.070
So we have π₯ cubed minus two is equal to negative π¦.
00:00:36.420 --> 00:00:39.060
Now we wanna isolate π¦ and get it by itself.
00:00:39.120 --> 00:00:42.340
So letβs go ahead and divide by the negative one everywhere.
00:00:42.950 --> 00:00:45.560
Essentially, weβre just changing the sign on every term.
00:00:45.820 --> 00:00:50.110
So we have π¦ equals negative π₯ cubed plus two.
00:00:50.760 --> 00:00:54.160
Or it could be written as π¦ equals two minus π₯ cubed.
00:00:54.350 --> 00:01:02.550
And now we replace π¦ with π inverse π₯, so the inverse of our function would be two minus π₯ cubed.